PENYIMPANGAN KEKUASAAN PADA PEJABAT PUBLIK DAPAT BERUPA PENYALAHGUNAAN WEWENANG YANG DIKATEGORIKAN SEBAGAI TINDAK PIDANA KORUPSI - Adriani Adnani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Power deviation in public officials can be in the form of abuse of authority which is categorized as a criminal act of corruption as can be seen in Article 2 paragraph (1) and Article 3 of Law Number 31 Year 1999 concerning Eradication of Corruption Crimes. These two articles regulate the misuse of authority by someone who has a position or position where the result of his actions is detrimental to the state's finances. Especially after the establishment of Law Number 30 of 2014 concerning Government Administration wherein Article 87 letter a stated that government factual actions as part of the meaning of state administrative decisions (KTUN) and Article 85 which states the existence of a transfer of settlement of government administrative disputes from public courts to administrative court. The provisions of Article 85 and Article 87 letter a above, are actually still vague (absurd norms) because there is no authentic explanation of the conception of factual action as the new meaning of the KTUN in Article 87 letter a, even though the two types of government actions are different in terms of administrative law the resolution of government administrative disputes from the general court to the Administrative Court is not stated clearly and clearly what type of dispute is transferred as referred to in the provisions of Article 85 of the AP Law.